A SCREENING OF KNOWLEDGE AND EDUCATION ON THE SIGNS AND SYMPTOMS OF CARDIAC ARREST AMONG THE GENERAL PUBLIC IN COASTAL AREAS: SKRINING PENGETAHUAN SERTA EDUKASI TANDA DAN GEJALA HENTI JANTUNG PADA MASYARAKAT AWAM DI WILAYAH PESISIR - Sulupadang, Prishilla; Tahir, Rusna; Rini, Dewi Sartiya (Poltekkes Kemenkes Kendari, 2025)
Background: Most cardiac arrests occur outside of hospitals. Cardiac arrest occurs when the heart suddenly and unexpectedly stops pumping, and hypertension is one of the causes. It is essential to have sufficient knowledge about the various adverse effects that can be caused by hypertension, often referred to as the “silent killer” because it often does not show symptoms but can have serious consequences if not managed properly, one of which is the risk of sudden cardiac arrest. The purpose of this knowledge screening is to [FW1] increase public awareness of the signs and symptoms of cardiac arrest as a preventive measure and to improve the quality of life of the community. The methods used include effective communication through pre- and post-knowledge screening, as well as education through counseling [FW2] [FW3] and demonstrations. The results of the knowledge screening from 25 respondents showed that the pre-test knowledge of the Bajo Indah village community regarding the signs and symptoms of cardiac arrest was still insufficient, with 16 respondents (64%) scoring below average. However, after receiving education, the post-test scores showed an increase in knowledge, with 22 respondents (88%) scoring above average. Conclusion: The implementation of this activity was able to increase the knowledge of the public in Bajo Indah Village regarding the signs and symptoms of cardiac arrest, which will serve as the basis for preventive efforts against cardiac arrest and improve the quality of life of the community.